IDENTIFICATION OF AQPS IN CHINESE HAMSTERS AND THEIR EXPRESSION PATTERNS IN TESTES OF DIFFERENT WEIGHTS - Shuo Wang; Jinhui Xu; Yongzhen Feng; Xingchen Wang; Huiliang Xue; Ming Wu; Laixiang Xu (Journal of Animal and Plant Sciences, 2024)
Aquaporins (AQPs) are a class of proteins encoded by MIP gene family, which play a critical role in maintaining cell morphology and small molecule transmembrane transport. In recent years, the role of AQPs in reproduction has gradually been revealed. They have been proved to be widely expressed in many species. The testicles of Chinese hamsters have the characteristics of large size and long spermatogenic cycle. This seems contradictory in evolution and has not been fully studied. At present, the whole genome analysis of AQPs in Chinese hamsters and the expression patterns in testes have not been reported. In this study, 13 AQPs were identified and characterized in the genome of Chinese hamster for the first time. Protein sequence analysis of AQPs showed that its structure and function were unified. The concentrations of testosterone are higher in larger testes. The expression patterns of AQPs in testes were different. AQP5, AQP7 and AQP11 were positively correlated with testicular weight. Sperm count showed that larger testes could produce more sperm and store it in epididymis. It is speculated that under the regulation of testosterone, AQPs affect the excretion of excess substances at the end of spermatogenesis, and adapt to the reproductive competition of Chinese hamsters by regulating the rate of spermatogenesis. The results provide basic resources for further studying the role of AQPs in spermatogenesis of Chinese hamster.
Keywords: Chinese hamster; Testis; Reproduction competition; AQPs